Gender Role Ideology in Pixar’s “Wall-E” and “Monsters University” - Rosalia Tania Putri (Institute of Research and Community Outreach - Petra Christian University, 2017)
Animation films have increasingly evolved throughout the years. No longer just a medium to convey stories, films also become an agent to express one’s beliefs. In this thesis, I discuss how Pixar demonstrates their ideal gender role through their films, Wall-E and Monsters University, with the assumption that Pixar deconstructs traditional gender role to show Pixar’s belief that a character can only be successful when he or she is able to adopt traits from both extremes. In order to accomplish this, I use gender role theory. In the analysis, I find out that both films’s existing ideology is that masculine gender role traits are put in higher hierarchy. However, the main characters’s characterization shows gender role traits which debunk the existing ideology such that both masculine and feminine traits become equally important to adopt. As a result, I can see that Pixar supports androgyny through their main characters. I also discover that their ideology can be used for increasing their profit income.